1979
DOI: 10.1136/hrt.41.5.600
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological and haemodynamic basis for application of new pacemaker technology in sick sinus syndrome and atrioventricular block.

Abstract: SUMMARY A fundamental description of pacemaker systems which are commercially available or in clinical validation is given as a background for their application in a series of 62 consecutive patients presenting over a period of 1 year for permanent cardiac pacing. The patients (23 (37%) sick sinus syndrome, 38 (61%) atrioventricular block, and 1 ventricular tachycardia) were studied electrophysiologically and haemodynamically to allow the appropriate application of a pacemaker system. In sick sinus syndrome, 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1981
1981
1992
1992

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Ten (7)(8)(9)(10)(11)(12) weeks after the implantation of a permanent pacemaker measurements at rest and during exercise were repeated. No significant change in all the basic hemodynamics oc-curred during this period (Table II).…”
Section: Long-term Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten (7)(8)(9)(10)(11)(12) weeks after the implantation of a permanent pacemaker measurements at rest and during exercise were repeated. No significant change in all the basic hemodynamics oc-curred during this period (Table II).…”
Section: Long-term Resultsmentioning
confidence: 99%
“…Testing in the asynchronous mode was not possible in the 2 patients with the Medtronic SPO-069 units and in one patient with SiemensElema 625. During this investigation no complications occurred; all pacemakers are working normally after a follow-up period of 12.7 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) months. Table I summarizes the results obtained in 76 studies of 10 patients with and without A-V synchrony at rest and at exercise.…”
Section: Methodsmentioning
confidence: 97%
“…The detection of impaired AV conduction is also of relevance for some SND patients in whom a more advantageous hemodynamic situation is provided by atrial rather than ventricular pacing (28).…”
mentioning
confidence: 99%
“…The effect of atrial contribution to ventricular stroke volume of the paced heart has been extensively studied in the experimental animaP5-18 and in man. [19][20][21][22][23][24] It could be shown that not only AV synchronization, as such, was important but the optimal timing of atrial contraction during the diastolic period as well. Measuring stroke volume beat by beat by means of impedance cardiography in patients with ventricular pacemakers implanted for complete AV block, Knapp et a1.…”
Section: Significance Of Av Synchronymentioning
confidence: 99%